The Effectiveness of a Training Model Based on Sufism for Enhancing Self-esteem - Julaikhah, Astin; Sarkadi, Sarkadi; Muhab, Sukro (Journal of International Conference Proceedings, 2023)
The goal of this investigation was to discover the effectiveness of Sufism-based training in increasing the self-esteem of elementary school teachers. This study uses a qualitative and quantitative approach. This research uses a quasi-experimental method. This study's sample consisted of public elementary school instructors in the South Jakarta area in DKI Jakarta Province, with a total of 50 teachers. The experiment in this study was the provision of interventions using training techniques or tasawuf-based training. Researchers conducted measurements (pre-test) and post-test.The results showed that the Sufism-based training model given to teachers proved beneficial in raising elementary school teachers' self-esteem in the South Jakarta area of DKI Province. This condition can be seen from the results of the tests carried out either through the t test, or the test using the n gain score. The tests that have been carried out are pretest and posttest.